PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 28 PADANG - Widiawati, Sri; Delsi K, Delsi K; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACTThis research background by students comprehension of mathematical concepts that were still low. The students didnât want to express their own idea, so they didnât want to ask about the unknown concepts. This researchâs purpose is to make sure that students comprehension of mathematical concepts using active learning strategy by Giving Question and Getting Answer is better than students comprehension of mathematical concepts using conventional learning for grade VIII students of SMP 28 Padang. This method of research was experiment research with random to the subject. The population research is grade VIII students of SMPN 28 Padang except class VIII.1 that was the superior class. Analysis technique used was t test one party by MINITAB and the result was P-value less than , so it can conclude that students comprehension of mathematical concepts using active learning strategi by Giving Question and Getting Answer was better than using conventional learning for grade VIII of SMPN 28 Padang.